Karakteristik Jasper Merah di Pulau Jawa Bagian Selatan Berdasarkan Analisis SEM dan XRF - Wijayanti, Kemala; Rosana, Mega Fatimah; Yuningsih, Euis Tintin; Sulistyawan, Raden Isnu Hajar (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Jasper is one type of microcrystalline silica which include to gemstone variety. Indonesia has a high potential of jasper because its variety and a huge number of jasper that widely spread in Indonesia. There are 3 (three) types of jaspers that usually found in Indonesia, red jasper, yellow jasper, and green jasper. Among three of them, red jasper is much more abundant especially in Southern Java.Therefore, this research was held to observe the differences of red jasper's characteristic in three places in Java, i.e., Bungbulang – Garut, Samigaluh – Yogyakarta, and Donorojo – Pacitan areas. To attain the purpose of this research, SEM analysis is used to compare their textures and XRF for the chemical compositions.The research concludes that the red jaspers from those three places have the same texture, the granulated texture which derived from quartz texture. The grain size seems to increased from west to east. From the chemical composition it can be seen that the red color of jasper is strongly affected by Fe, Cr, and V. The Ti elements of red jasper also increased from west to east because there is a high Ti content in Pacitan's red jasper and perhaps by the combination of those elements resulting the purple color in red jasper.Keywords - red jasper, gemstone, composition, element, Southern Java